Historical Development of Legal Aid System in India: A Legal Perspectives. (January 2023) - Nazim, Sohail
Human civilisation has always been plagued by the problem of access to justice for the weak. With human development, the modern state took up the responsibility of administering justice. Modern states have complex legal systems, making legal aid an essential part of access to justice for the poor. In 1976, the Indian Constitution was amended to add Article 39A, mandating the state's responsibility to provide free legal aid to the impoverished. Legal aid is discussed in the article, along with its origins and meaning. This article examines the history and legal framework of legal aid in India. Further, a judicial analysis is provided that makes legal aid a fundamental right. The article also emphasises the lacunas in the judicial system in India.